Women Choice of Traditional Birth Attendants in Childbirth and Factors Associated - Shinta Novelia; Tommy J Wowor; Dwi Sulistyowati (KHD Production, 2023)
The number of birth deliveries attended by unskilled traditional birth attendants was still high. A lot of women like to do ANC, but eventually, they choose traditional birth attendants to help them in the childbirth process. The research aims to analyze factors related to women's choice of traditional birth attendants in the childbirth process at the work area of Bandung Health Center, Serang, Banten, in 2018. This is descriptive quantitative research with a cross-sectional approach. The population is 115 women who gave birth in the work area of Bandung Health Center, Serang, Banten, during May and June of 2018. The sample is a total population. The dependent variable is the women's choice of traditional birth attendants, and the dependent variables are education, knowledge, socio-economic status, and the distance of the women's houses to the Health Center. The results show that among all independent variables, three of them are related to women's choice of birth attendants in childbirth. They are education (p=0.036), knowledge (p=0.015), and Accessibility to Health Care Facility (p=0.008). There is no relationship between socioeconomic status and women's choice of birth attendants in childbirth (p=0.148). Future research should explore more variables that might contributed to women's choice of traditional birth attendants. Education intervention is needed to increase the knowledge of the community regarding the importance of using healthcare facilities during childbirth.